2020
DOI: 10.3389/fphy.2020.622551
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Concentration of Fe and Cu Nanoparticles on the Dynamics of the Size Distribution of Nanoparticles

Abstract: The evolution of the size distribution of nanoparticles depending on the concentration of nanoparticles in a colloidal solution is investigated. The formation of new stable distributions shifted relative to the initial distribution is directly related to the processes of agglomeration of nanoparticles. Using successive two-fold dilutions of nanoparticles by 2–32 times, it was shown that the maximum of the nanoparticle size distribution shifts toward smaller sizes with a decrease in the concentration of nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
1
4
0
2
Order By: Relevance
“…The result showed that the higher concentration of AgNO3, the bigger particle size of AgNP, as shown at Table 3, respectively. This result was in accordance to the previous study which combination of high concentration and high temperature produced AgNP with bigger particle size (19,20).…”
Section: Synthesis and Characterization Of Silver Nanoparticlessupporting
confidence: 93%
“…The result showed that the higher concentration of AgNO3, the bigger particle size of AgNP, as shown at Table 3, respectively. This result was in accordance to the previous study which combination of high concentration and high temperature produced AgNP with bigger particle size (19,20).…”
Section: Synthesis and Characterization Of Silver Nanoparticlessupporting
confidence: 93%
“…It should be noted that the degree of aggregation of colloidal dispersions depends not only on the NP characteristics, including size, surface charge and composition, but also on their concentration. For instance, recently, it was shown that using Fe NPs, the aggregation rate increases by increasing iron concentration [44]. It is difficult to quantify the impact of such effect in complex systems such as biological media; however, colloidal stability should be carefully checked during the experiments, and this unavoidable effect needs consideration when interpreting the data.…”
Section: Discussionmentioning
confidence: 99%
“…Было обнаружено, что скорость образования АФК возрастает экспоненциально при увеличении частоты механического воздействия. Основные способы генерации пероксида водорода, вероятно, связаны с образованием синглетного кислорода и его дальнейшим восстановлением, а альтернативным путем является образование перекиси водорода в результате рекомбинации гидроксильных радикалов [121]. Как правило, сразу после механического воздействия рН воды повышается.…”
Section: обработка с помощью вихревого перемешивания встряхивания и и...unclassified